A genotype–phenotype correlation study reveals that a non‐coding RNA might be associated with cardiovascular anomalies in fetuses with WHS. (19th August 2016) - Wu, Yi; Tao, Jiong; Wang, Yan‐Lin; Hu, Wen‐Jing; Han, Xu; Cheng, Wei‐Wei
Abstract : What's Already Known About This Topic? Wolf–Hirschhorn syndrome is a genetic disorder caused by partial deletion of the short arm of chromosome It consists of a broad spectrum of clinical manifestations. The deletion size also varies significantly. What Does This Study Add? This study found that a non‐coding RNA (NR_130734) might be involved in cardiovascular development by analyzing the genotype–phenotype correlation of two fetuses with Wolf–Hirschhorn syndrome.